Rancher Perspectives of a Livestock-Wildlife Conflict in Southern Chile - Hernández, Fidel; Corcoran, Derek; Graells, Giorgia; Rios Cardoza, Carlos Francisco; Downey, M.C. (My University, 2017)
Biodiversity is an important ecosystem service provided by rangelands. However, the close link between biodiversity and rangelands often results in conflicts between human livelihood and biological conservation, as is occurring with the livestock-guanaco (Lama guanicoe) conflict in Patagonia, Chile.• Understanding community attitudes and perspectives regarding conservation is critical for successful conservation. We conducted a study to assess rancher perspectives of traditional land-use practices and biological conservation to identify incentives for, and barriers to, guanaco conservation.• Ranchers strongly valued biodiversity and demonstrated stronger support for the cultural value, rather than economic value, of guanacos. However, a negative perception was associated with guanacos, and guanaco overabundance was identified as the primary cause of the conflict.• Use of a sustainable-harvest approach of guanaco products, which emphasizes the commercial value of guanacos, may not be an effective conservation tool for the species under current conditions. Moreover, identifying the cultural carrying capacity, ecological carrying capacity, and minimum viable population of guanacos will be important in guiding conflict resolution.
Keywords: chile; guanaco; livestock-wildlife conflict; patagonia; ranching; tierra del fuego